Hydraulic Performance of Drip Irrigation System with Municipal Wastewater - Tripathi, Vinod Kumar; Rajput, T.B.S; Patel, Neelam; Lata, Lata (Journal of Agricultural Engineering, 2011)
Generation of wastewater in huge amounts is putting a lot of pressure on irrigation engineers for its safe disposal or reuse in agriculture. Though wastewater could contribute to major and minor nutritional requirement of crops, but the presence of microbial contaminants and toxic elements limits its use. Utilization of wastewater for irrigation through drip irrigation system seems to be a good choice to reduce the chances of contamination due to restricted quantity of water application. Since clogging in such a situation would be the main problem, its remediation is required for enhanced utilization of wastewater through drip irrigation system. Physical and chemical characteristics of wastewater were determined and compared with ground water. While higher EC, pH, Mg, and carbonate were observed in ground water, wastewater contained higher turbidity, total solids, HCO3 , and Ca. Population of total coliforms (2.72x104 to 5.2x107) and E. coli. (1.8x10Â³ to 2.64x106) were detected in wastewater. The hydraulic performance of drip emitters was studied for two years (2009 and 2010) with municipal wastewater and ground water using gravel media (F1), disk filter (F2) and combination of gravel and disk filters (F3). Filtration using F3 gave emitter discharge exponent close to 0.5 with RÂ² value of 0.99. Emitter flow rate decreased with increase in time of operation of the system. Coefficient of variation less than 4% with wastewater and ground water showed excellent performance in surface placed drip lateral after two years of operation. After filtration with F3, coefficient of variation (CVq) of 4.0 % with wastewater and 6.46 % with ground water was observed under subsurface (15 cm deep) placement of laterals.